2021
DOI: 10.1007/s42452-021-04452-4
|View full text |Cite
|
Sign up to set email alerts
|

Characteristical analysis of MHD heat and mass transfer dissipative and radiating fluid flow with magnetic field induction and suction

Abstract: This study is conducted on the magneto-hydrodynamics (MHD) boundary layer (BL) heat and mass transfer flow of thermally radiating and dissipative fluid over an infinite plate of vertical orientation with the involvement of induced magnetic field and thermal diffusion. The fluid motion is controlled by uniform suction. The constant heat and mass fluxes at the boundary (plate) have been considered to establish the boundary conditions. The foremost prevailing equations are converted into non-linear dimensionless … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…▪ The Mathematica and Wolfram codes are deployed in gaining the numerical solutions from analytical form. According to Poddar et al [29], the analogy of the Rosseland approximation in relation to the radiation heat fluctuation simplifies to…”
Section: Methods Of Solutionmentioning
confidence: 99%
“…▪ The Mathematica and Wolfram codes are deployed in gaining the numerical solutions from analytical form. According to Poddar et al [29], the analogy of the Rosseland approximation in relation to the radiation heat fluctuation simplifies to…”
Section: Methods Of Solutionmentioning
confidence: 99%
“…Some successful studies within a similar calculation framework can be found in Refs. [26][27][28][29][30][31].…”
Section: Calculation Techniquementioning
confidence: 99%
“…Their results show that by raising the levels of Rayleigh number, the heat transfer amount is improved, but with the growing power‐law index and Hartmann number, the heat transfer rate diminishes for shear thinning, Newtonian, and shear thickening fluids. Using an efficient explicit finite difference method, Poddar et al 31 investigated the analysis of MHD boundary layer convective flow of heat radiating and dissipative fluid past an immeasurable plate of vertical shape having an IMF and Soret effect. They revealed that a rising magnetic parameter suppresses the IMF.…”
Section: Introductionmentioning
confidence: 99%